2015
DOI: 10.1016/j.ijgo.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Maternal bacteremia and the Irish maternity early warning system

Abstract: Among pregnant women with proven bacteremia, introduction of IMEWS has been associated with an improvement in the recording of vital signs, particularly respiratory rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
7
19
0
Order By: Relevance
“…The completion of the RI and MEOWS tool by 77% of participants suggests an adequate feasibility. Our result was consistent with other previous studies although the level of completeness of our study was not as substantial as in other studies like the study done in UK, Ireland, and Zimbabwe that reported an improvement in the frequency of documentation of vital signs, the time interval between trigger and antibiotic administration, and pre-operative stabilization of women undergoing caesarean section following the implementation of the Early Warning Signs (EWS) tool (Cantwell et al, 2008;Maguire et al, 2015;Merriel et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The completion of the RI and MEOWS tool by 77% of participants suggests an adequate feasibility. Our result was consistent with other previous studies although the level of completeness of our study was not as substantial as in other studies like the study done in UK, Ireland, and Zimbabwe that reported an improvement in the frequency of documentation of vital signs, the time interval between trigger and antibiotic administration, and pre-operative stabilization of women undergoing caesarean section following the implementation of the Early Warning Signs (EWS) tool (Cantwell et al, 2008;Maguire et al, 2015;Merriel et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that early recognition of patients at high risk of complications might allow earlier transfer before the development of complications and speed up the access to care at higher level by minimizing delays through easy situation awareness, communication, and decision making among teams. For example, studies done in Ireland and Zimbabwe reported an improvement in the time interval between trigger and antibiotic administration, and pre-operative stabilization of women undergoing caesarean section following the implementation of the Early Warning Signs (EWS) tool (Maguire et al, 2015;Merriel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…3 Others trigger the same response when one or more markedly abnormal, or two or more mildly abnormal, observations are present. 13,14 These systems are frequently used alongside charts featuring colour-coded shading to highlight the markedly and mildly abnormal vital signs ranges, often shaded in red and yellow, respectively ( Figure 1). 1, 15 A third type of ObsEWS allocates points in a weighted manner, based on the derangement of a woman's measured vital signs from pre-defined 'normal' ranges (Table 1).…”
Section: -10mentioning
confidence: 99%
“…This suggests that early recognition of patients at high risk of complications might allow earlier transfer before the development of complications and speed up the access to care at higher level by minimizing delays through easy situation awareness, communication, and decision making among teams. For example, studies done in Ireland and Zimbabwe reported an improvement in the time interval between trigger and antibiotic administration, and preoperative stabilization of women undergoing caesarean section following the implementation of the Early Warning Signs (EWS) tool [4,5].…”
Section: Introductionmentioning
confidence: 99%